Edukasi Dukungan Sosial terhadap Orang dengan Risiko Tinggi HIV/AIDS di SMK Bhakti Kencana Ciamis - Nur Hidayat; Nida Farhatul Muslihah; Ayu Khodijah Yuliana; Kemuning; Arfani Rahman; Mochammad Arkan Haidar Amru; Ajeng Sonya (KOLABORASI JURNAL PENGABDIAN MASYARAKAT, 2022)
Introduction: Problems in Indonesia that arise due to poor health behavior, one of which is HIV/AIDS, in the Ciamis district there were 95 cases of HIV/AIDS in 2019. AIDS itself is a symptom of damage to the immune system due to a virus called Human Immunodeficiency or called HIV. For sufferers, getting social support from the environment will really help them in developing themselves. Objective: This activity aims to provide counseling that people with HIV/AIDS need social support from their families and their environment, it is also hoped that at the end of the counseling process students can understand HIV/AIDS and how to provide social support to people at risk of getting HIV/AIDS. Method: The method used in this counseling is the lecture method using PowerPoint media. Result: Based on the evaluation there is an increase in knowledge about HIV/AIDS and how to provide social support to people at risk of getting HIV/AIDS. The results of the evaluation of extension activities showed that 5 out of 24 students responded to the questions given and could answer questions correctly.  Conclusion:  An increase in knowledge about HIV/AIDS and how to provide social support to people at risk of HIV/AIDS with indicators that students understand the material provided, can answer questions, and provide appropriate answers. Suggestions for this activity need to be improved in preparing for the activities to be carried out.